EARTHQUAKE SIMULATION METHOD IN MAN 1 SRAGEN - Rizaldy, David; Trimasukmana, Danang Junior (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This study aims to determine whether there is an influence and the magnitude of the effect of the use of earthquake simulation learning methods on learning outcomes in geography subjects XI IPS MAN 1 Sragen. Researchers collected data using questionnaires, tests, observations, and documentation. Data analysis techniques using percentage descriptive analysis and simple linear regression analysis. The results showed the experimental class obtained cognitive learning outcomes of 87.7%, affective learning outcomes of 90.74%, and psychomotor of 93.00%. Then the control class got 79.94% cognitive learning outcomes, affective 59.76%, and psychomotor at 62.43%. The conclusion of this study is